Physiological phenotyping of human frailty - Taylor, Joseph (2024)
Frailty is an age-related syndrome characterised by an enhanced vulnerability to adverse health outcomes compared to the non-frail state. However, the physiological phenotype of frailty is poorly understood. This thesis aimed to provide novel insight into the frailty phenotype, thus identifying physiological targets for further research into mechanisms driving frailty progression. A deep physiological phenotyping study was performed in older (aged 65-91 years) non-frail, pre-frail and frail females with no overt disease. Frailty status was defined using the Physical Frailty Phenotype criteria: weakness, slowness, exhaustion, weight loss and low physical activity. Participants were deemed non-frail if no criteria were present, pre-frail if one or two criteria were present, or frail if three or more components were present. Assessments of physical function, neuromuscular characteristics and multi-organ MRI were performed.